Ampicillin Pharmacokinetics in Peripartum and Laboring Women - Judy, Amy E.; Frymoyer, Adam; Ansari, Jessica; Drover, David R.; Carvalho, Brendan (American Journal of Perinatology, 2021)
Objective Ampicillin is used for multiple peripartum indications including prevention of neonatal group B streptococcus (GBS) and treatment of chorioamnionitis. Despite its widespread use in obstetrics, existing pharmacokinetic data for ampicillin do not address contemporary indications or dosing paradigms for this population. We sought to characterize the pharmacokinetic profile of ampicillin administered to laboring women.Study Design Using whole blood dried blood spot sampling technique, maternal blood samples were collected at specified times from 31 women receiving intravenous (IV) ampicillin for peripartum indications. Women received either a 2-g loading dose with 1-g administered every 4 hours (GBS) or 2-g every 6 hours (chorioamnionitis). Pharmacokinetics were analyzed via a population approach with nonlinear mixed-effect modeling.Results The data were best described by a two-compartment model with first-order elimination, with the following whole blood parameters: central volume of distribution (V1), 75.2 L (95% confidence interval [CI]: 56.3–93.6); clearance (CL), 82.4 L/h (95% CI: 59.7–95.7); intercompartmental clearance (Q), 20.9 L/h (95% CI: 16.2–38.2); and peripheral volume of distribution (V2), 61.1 L (95% CI: 26.1–310.5). Interpatient variation in CL and V1 was large (42.0 and 56.7%, respectively). Simulations of standard dosing strategies demonstrated over 98% of women are predicted to achieve an estimated free plasma concentration above mean inhibitory concentration (MIC) of 0.5 μg/mL for more than 50% of the dosing interval.Conclusion Although large variation in the pharmacokinetics of ampicillin in pregnant women exists, as predicted by our model, current standard dosing strategies achieve adequate exposure for GBS in nearly all patients.Key Points
Keywords: antibiotics; pharmacokinetics; placenta; ampicillin; obstetrics; pregnant; dried blood spot sampling; group B streptococcus